Addition of adjuvant hepatic artery infusion to systemic chemotherapy following resection of colorectal liver metastases is associated with reduced liver‐related mortality. Issue 8 (31st March 2020) - Srouji, Rami; Narayan, Raja; Boerner, Thomas; Buisman, Florian; Seier, Ken; Gonen, Mithat; Balachandran, Vinod P.; Drebin, Jeffrey; Jarnagin, William R.; Kingham, T. Peter; Wei, Alice; Kemeny, Nancy E.; et al.
Abstract: Background: After resection of colorectal liver metastases (CRLM), recurrent disease in the liver is a major cause of death but may be reduced with the addition of adjuvant hepatic arterial infusion (HAI) chemotherapy to systemic chemotherapy (SYS). Objective: This study investigates organ‐specific causes of death in patients receiving adjuvant HAI and SYS compared to adjuvant SYS alone. Methods: Between 2000 and 2007, patients undergoing complete CRLM resection were identified from a prospectively maintained liver resection database and categorized as receiving HAI + SYS or SYS only. Using newly constructed definitions, mortality was attributed to specific organs (liver, lung, peritoneum, and brain) or infection. Univariate models and cumulative incidence functions were generated using competing risk methods. Results: Of 361 eligible patients, 208 (57.6%) received HAI + SYS and 153 (42.4%) received SYS. The median follow up among survivors was 142 months (range = 12‐217 months). Ten‐year overall survival was 50.6% in the HAI + SYS group compared to 30.9% in those receiving SYS ( P  = .004). The 5‐year cumulative incidence of liver‐related mortality was 6.8% in the HAI + SYS group compared to 14.3% in the SYS group ( P  = .007). Conclusion: The addition of HAI to SYS after CRLM resection is associated with a 50% reduction in liver‐related mortality at 5 years.